2011
DOI: 10.1088/1367-2630/13/10/103003
|View full text |Cite
|
Sign up to set email alerts
|

An optical fusion gate for W-states

Abstract: We introduce a simple optical gate to fuse arbitrary size polarization entangled W-states to prepare larger W-states. The gate requires a polarizing beam splitter (PBS), a half wave plate (HWP) and two photon detectors. We study numerically and analytically the necessary resource consumption for preparing larger W-states by fusing smaller ones with the proposed fusion gate. We show analytically that resource requirement scales at most sub-exponentially with the increasing size of the state to be prepared. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 39 publications
1
108
0
Order By: Relevance
“…A simple optical fusion gate has recently been introduced (though not experimentally demonstrated yet) which can fuse two arbitrary size W states and create a W state with a resource requirement increasing subexponentially with respect to the target size [25]. This "fusion gate" for W states consists of a polarization beam splitter (PBS), a half wave plate (HWP) and two photon detectors.…”
Section: W State Preparation Via Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple optical fusion gate has recently been introduced (though not experimentally demonstrated yet) which can fuse two arbitrary size W states and create a W state with a resource requirement increasing subexponentially with respect to the target size [25]. This "fusion gate" for W states consists of a polarization beam splitter (PBS), a half wave plate (HWP) and two photon detectors.…”
Section: W State Preparation Via Fusionmentioning
confidence: 99%
“…It is generally desired that the fusion operation succeeds by accessing only one qubit from each state as this reduces the complexity of the fusion operation, making it more experimentally feasible. Here, studies have shown that two W states, GHZ states, or cluster states can be fused together to form a larger state with the same entanglement structure as the input states by accessing only one qubit from each of the initial states and these initial states can also be expanded by adding one or two qubits at a time by locally accessing only one of their qubits [20,[25][26][27][28][29]. However, for Dicke states this is not the case [30] and there has not yet been a proposal for such a fusion gate for these states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since multipartite entanglement creation and processing may be used in computation problems, it is one of the hot topics in quantum information domain [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. QFI may be considered a first general entanglement measure for multipartite systems and some meaningful research activities continue in this aspect [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Construction and processing of multi-partite entangled states, state ordering and relation with quantum Fisher information is a hot topic in related research areas. [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%